Placenta-mediated pregnancy complications in women with a history of late fetal loss and placental infarction without thrombophilia: risk of recurrence and efficacy of pharmacological prophylactic interventions. A 10-year retrospective study. (31st December 2023) - Borella, Fulvio; Marozio, Luca; Bertschy, Gianluca; Botta, Giovanni; Bertero, Luca; Cassoni, Paola; Maina, Aldo; Cosma, Stefano; Benedetto, Chiara
Abstract: Purpose: To evaluate the risk of recurrence of severe placenta-mediated pregnancy complications and compare the efficacy of two different anti-thrombotic regimens in women with a history of late fetal loss without thrombophilia. Patients and methods: We performed a 10-year retrospective observational study (2008–2018) analyzing a cohort of 128 women who suffered from pregnancy fetal loss (>20 weeks of gestational age) with histological evidence of placental infarction. All the women tested negative for congenital and/or acquired thrombophilia. In their subsequent pregnancies, 55 received prophylaxis with acetylsalicylic acid (ASA) only and 73 received ASA plus low molecular weight heparin (LMWH). Results: Overall, one-third of all pregnancies (31%) had adverse outcomes related to placental dysfunction: pre-term births (25% <37 weeks, 5.6% <34 weeks), newborns with birth weight <2500 g (17%), and newborns small for gestational age (5%). The prevalence of placental abruption, early and/or severe preeclampsia, and fetal loss >20 weeks were 6%, 5%, and 4% respectively. We found a risk reduction for combination therapy (ASA plus LMWH) compared with ASA alone for delivery <34 weeks (RR 0.11, 95% CI: 0.01–0.95 p = 0.045) and a trend for the prevention of early/severe preeclampsia (RR 0.14, 95% CI: 0.01–1.18, p = 0.0715), while no statistically significant difference was observed for composite outcomes (RR 0.51, 95%CI: 0.22–1.19, p = 0.1242). An absolute risk reduction of 5.31% was observed for the ASA plus LMWH group. Multivariate analysis confirmed a risk reduction for delivery <34 weeks (RR 0.32, 95% CI 0.16–0.96 p = 0.041). Conclusion: In our study population, the risk of recurrence of placenta-mediated pregnancy complications is substantial, even in the absence of maternal thrombophilic conditions. A reduction of the risk of delivery <34 weeks was detected in the ASA plus LMWH group.